Characteristics and Kinematics of Fresh Belgian Blue Semen and Its Resistance to Frozen–Thaw Using Different Extenders - A. M. N. Maulidyah; M. Agil; S. Said; T. P. Nugraha; R. I. Arifiantini (Tropical Animal Science Journal, 2026)
Extenders are used to preserve semen quality during storage. The Belgian Blue is a cattle breed known for its high dressing percentage; however, male reproductive performance is relatively low due to small testes size. This study aimed to analyze the characteristics and kinematics of fresh and frozen Belgian Blue semen. Fresh semen samples were collected from four Belgian Blue bulls, and their quality was assessed macroscopically, microscopically, and kinematically using portable computer-assisted sperm analysis (CASA) immediately after collection. Semen samples with progressive sperm motility ≥70% were diluted with the following extenders: Tris–egg yolk (TEY) and the commercial extenders AndroMed®, BoviFree®, and Steridyl®. CASA results showed that bulls differed significantly in ejaculate volume, color, consistency, sperm kinematics, including velocity curvilinear (VCL), velocity straight-line (VSL), and velocity average path (VAP), and sperm motility; however, none of these variables differed among frozen–thawed semen samples treated with the different extenders. In contrast, total motility, slow motility, and immotile sperm in frozen–thawed semen differed significantly between bulls. In conclusion, the characteristics of fresh Belgian Blue semen vary between individuals. Moreover, TEY, AndroMed®, BoviFree®, and Steridyl® showed comparable protective capabilities for frozen–thawed semen.